2021
DOI: 10.1101/2021.11.06.21265920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mono- and bi-allelic effects of coding variants on disease in 176,899 Finns

Abstract: Identifying Mendelian diseases with recessive inheritance is challenging as the majority of cases are caused by compound heterozygous genotypes which require sequencing data in families to definitively identify. Bottleneck events, such as in the Finnish population, enrich specific homozygous variants to higher frequencies and thus facilitate identification of disease associations through easily recognized homozygous genotypes. Here, we study homozygous and heterozygous effects of 82,516 coding variants on 2,44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Via simulations, we show that the associations we detected are unlikely to be due to autozygosity increasing additive variance for genetic risk of binary traits, suggesting wide-spread non-additive effects. In the few studies that have looked, recessive-acting rare and common variants have been found to be associated with multiple common diseases including T2D [45][46][47] . However, it has been previously shown that dominance heritability at common variants is negligible 48,49 , suggesting the observed F ROH associations likely stem from non-additive effects at low allele frequency variants and/or epistasis.…”
Section: Discussionmentioning
confidence: 99%
“…Via simulations, we show that the associations we detected are unlikely to be due to autozygosity increasing additive variance for genetic risk of binary traits, suggesting wide-spread non-additive effects. In the few studies that have looked, recessive-acting rare and common variants have been found to be associated with multiple common diseases including T2D [45][46][47] . However, it has been previously shown that dominance heritability at common variants is negligible 48,49 , suggesting the observed F ROH associations likely stem from non-additive effects at low allele frequency variants and/or epistasis.…”
Section: Discussionmentioning
confidence: 99%
“…These associations demonstrate that imputation using a population specific genotyping array and imputation panel combined with national registry-based phenotyping in the isolated Finnish population can successfully identify associations and fine-map causal variants even in rare variants and phenotypes. An extended study of ClinVar variants as well as variants with novel bi-allelic Mendelian effects in FinnGen is described in an accompanying paper by Heyne et al 22 .…”
Section: Known Rare and Low-frequency Pathogenic Variant Associationsmentioning
confidence: 99%
“…There are also examples where the allele frequency of a certain variant is much smaller in Finns than in an admixed European sample, and vice versa, while there are variants enriched in Finns that occur at much lower frequencies in the European population. The preprint by Heyne et al (2021) suggests that Finnish genomes harbor fewer detectable variants for recessively inherited disease variants than non-Finnish Europeans, but those that are detected have larger MAFs. Therefore, alongside the FDH, Finnish genomes are also enriched for variants linked to more genetically complex diseases, which can facilitate discoveries in the common complex disease spectrum with implications beyond this single population.…”
Section: Justification For Studying Genetic and Clinical Data In Finlandmentioning
confidence: 99%